2008
DOI: 10.1007/s00276-008-0346-1
|View full text |Cite
|
Sign up to set email alerts
|

Metrical and non-metrical study of anterior clinoid process in South Indian adult skulls

Abstract: The result of the present investigation suggests that ACPs of South Indian skulls are highly variable and, are marginally larger and thicker than ACPs of Nepalese and Korean origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 19 publications
3
10
1
1
Order By: Relevance
“…Gupta et al (2005) (9) observed the mean length of ACP in Nepalese dry skulls on the right side as 10.74 ± 2.37 and on left side as 10.83 ± 1.20, which were slightly less than the length of ACP in North Indian dry skulls. A study by Kapur and Mehić, (7) on 200 dry skulls from Sarajevo and Bosnia average length was 9.9 ± 1.6 mm and 8.7 ± 1.5 mm on right and 9.3 ± 1.4 and 8.3 ± 2.1 mm on left side in males and females skulls respectively, which was less as compared to the North Indian skulls and comparable to a South Indian study done by Shahin Hunnargi et al (2008), (10) in their metrical and non-metrical study with mean length of 10.68 ± 1.9 mm and 9.96 ± 1.71 mm on right and left side respectively.…”
Section: Discussionsupporting
confidence: 68%
“…Gupta et al (2005) (9) observed the mean length of ACP in Nepalese dry skulls on the right side as 10.74 ± 2.37 and on left side as 10.83 ± 1.20, which were slightly less than the length of ACP in North Indian dry skulls. A study by Kapur and Mehić, (7) on 200 dry skulls from Sarajevo and Bosnia average length was 9.9 ± 1.6 mm and 8.7 ± 1.5 mm on right and 9.3 ± 1.4 and 8.3 ± 2.1 mm on left side in males and females skulls respectively, which was less as compared to the North Indian skulls and comparable to a South Indian study done by Shahin Hunnargi et al (2008), (10) in their metrical and non-metrical study with mean length of 10.68 ± 1.9 mm and 9.96 ± 1.71 mm on right and left side respectively.…”
Section: Discussionsupporting
confidence: 68%
“…Andaluz et al (2006), reported relatively small values for both height (8.67±2.63 mm) and width (6.57±1.68 mm). Hunnargi et al (2008), reported in their dry skull study, differences between South Indian, Nepalese and Korean ACP dimensions on both the right and left side. They found that the average length of the right ACP was 10.68±1.90 mm and that of the left Hayashi (2004) and by Gupta et al (2005).…”
Section: Discussionmentioning
confidence: 92%
“…The anatomical relationships of the ACP, ON, chiasm, internal carotid artery (ICA), ophthalmic artery (OA) and falciform ligament (FL) are complex and represent important variations. In the past three decades a number of researchers have examined some parts of the supra-and parasellar region, yet the anatomy of this area remains complex and varied (3,7,(9)(10)(11)(12)19,(22)(23)(24)29,31,32,34,35). This region also is one of the most common that can be affected by many neoplastic and vascular neurosurgical lesions.…”
Section: Anterior Klinoid Proçes Mikrocerrahi Anatomisi Ve Varyasyonlmentioning
confidence: 99%
“…The C5 segment of the ICA extends from the PDR to the DDR and lies immediately below the ACP. The DDR is a landmark for the end of the C5 segment and the beginning of the ophthalmic (C6) segment ( Figure 11) (19). The PDR loosely surrounds the ICA.…”
mentioning
confidence: 99%